2010
DOI: 10.1007/s10773-010-0286-5
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Fisher Information in the Generalized One-axis Twisting Model

Abstract: We investigate the quantum Fisher information (QFI) of symmetric states for spin-s particles. We derive the maximal QFI, and find that quantum spin correlations are essential ingredients of the maximal QFI. We make applications to the generalized one-axis twisting model. The results show that the redistributions of uncertainties on the basis of the quantum correlations in the multiqubit system are useful for sub-shot-noise phase sensitivity. Furthermore, for high-spin (s > 1/2) composite systems, we find a suf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 21 publications
0
22
0
Order By: Relevance
“…For even N when ∆J 2 n 3 = V + , F ϕ,max occurs in the n 3 direction [45]. In addition, with V − , we recover the analytical expression of ξ 2 K according to equation (18) given in [28].…”
Section: One-axis Twisting Modelmentioning
confidence: 85%
See 1 more Smart Citation
“…For even N when ∆J 2 n 3 = V + , F ϕ,max occurs in the n 3 direction [45]. In addition, with V − , we recover the analytical expression of ξ 2 K according to equation (18) given in [28].…”
Section: One-axis Twisting Modelmentioning
confidence: 85%
“…It has been numerically found that the maximal QFI for OAT-induced state is [45] F ϕ,max (t) = 4 max{V + , ∆J 2 n 3 }.…”
Section: One-axis Twisting Modelmentioning
confidence: 99%
“…where the operator S n is defined as S n = sin cos S x + sin sin S y + cos S z and max S 2 (x, y) indicates the maximum fluctuation in the plane (x, y) [14]. It is easy to calculate the fluctuations S 2 z and S 2 (x, y).…”
Section: Lemma 1 For the Symmetric Statementioning
confidence: 99%
“…To generate spin squeezing and spin squeezed states, Kitagawa and Ueda firstly introduced the one-axis twisting and the twoaxis countertwisting model [7]. Subsequently, the one-axis twisting model was widely studied [9,[11][12][13][14]. Some works show that one-axis twisting model with an external transverse field and two-axis countertwisting model with an external transverse field can improve spin squeezing and entanglement [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…If [S n 1 , S ⊥ ] + = 0, which means S n 1 and S ⊥ has no correlations under state ρ, we have [31] max(…”
Section: Quantum Fisher Information and Spin Squeezingmentioning
confidence: 99%